Chronology of reproductive investment determines predation risk aversion in a felid‐ungulate system. Issue 6 (26th February 2019) - Crawford, Daniel A.; Cherry, Michael J.; Kelly, Brian D.; Garrison, Elina P.; Shindle, David B.; Conner, L. Mike; Chandler, Richard B.; Miller, Karl V.
Abstract: Fear of predators can behaviorally mediate prey population dynamics, particularly when predation risk influences reproductive investment. However, the costs of reproductive investment may mitigate predation risk aversion relative to periods when the link between reproductive output and prey behavior is weaker. We posit that intensity of reproductive investment in ungulates may predict their response to predation risk such that the sexes increase risk exposure during biological seasons that are pivotal to reproductive success, such as the fawn‐rearing and breeding seasons for females and males, respectively. We examined the activity patterns of sympatric white‐tailed deer ( Odocoileus virginianus ), a sexually segregated polygynous ungulate, and Florida panthers ( Puma concolor coryi ) in the context of the "risky times – risky places hypothesis" and the reproductive strategy hypothesis. We compared detection rates and diel activity overlap of both species using motion‐triggered camera traps positioned on ( n = 120) and off ( n = 60) anthropogenic trails across five reproductive seasons. Florida panthers were nocturnal and primarily observed on‐trail providing an experimental framework with risky times and risky places. Contrary to studies in other taxa inversely correlating prey reproductive investment to predation risk, the sexes of deer were more risk prone during sex‐specific seasons associated with intense reproductive investment. Our results suggest spatiotemporally variable predation risk influences sex‐specific behavioral decision‐making in deer such that reproductive success is maximized. Abstract : We examined the activity patterns of sympatric white‐tailed deer ( Odocoileus virginianus ), a sexually segregated polygynous ungulate, and Florida panthers ( Puma concolor coryi ) in the context of the "risky times – risky places hypothesis" and the reproductive strategy hypothesis. Contrary to studies in other taxa inversely correlating prey reproductive investment to predation risk, the sexes of deer were least risk averse during sex‐specific seasons associated with intense reproductive investment. Our results suggest spatiotemporally variable predation risk influences sex‐specific behavioral decision‐making in deer such that reproductive success is maximized.